Nurturing the Environment on Senegal's West Coast - World Bank (Washington, DC, 2012)
The natural reserve of Ker Cupaam, is located along the Atlantic coast in Senegal, a fragment of a former national forest, basically for the protection of endangered species. Both the flora, and fauna had been severely damaged as a result of drought, grazing, and firewood harvest. Though constitution of the nature reserve in the 1980s, helped control further environmental degradation, the region's vegetation had been so severely damaged, that clearly intensive efforts were needed to restore its ecology, and attract tourism to benefit the local population. The creation of the Association of Women of Popenguine for the Protection of the Environment, took place in 1988, which used its own resources, and later additional donor assistance. Measures included the constitution of green firebreaks around the perimeter, replanting native species, and organizing workshops to learn about nature conservation in order to perform the required labor. This lead to measures for the provision of alternate sources of energy, and to achieve commercial self-sufficiency to obtain cooking fuel; a cooperative network would distribute wood, charcoal, and gas, and, regulate consumption; a village tree nursery, and forest conservation efforts begun; and, collection of household wastes for composting was established. Soon, surrounding villages were participating, and, new dimensions included credit and banking; tourist and training infrastructure; and, youth employment. The reserve now covers fifty square miles, and provide economic opportunities for bordering communities.